Thin film materials technology : sputtering of compound materials - Wasa, Kiyotaka (William Andrew Pub. ; Springer, 2004)
An invaluable resource for industrial science and engineering newcomers to sputter deposition technology in thin film production applications, this book is rich in coverage of both historical developments and the newest experimental and technological information about ceramic thin films, a key technology for nano-materials in high-speed information applications and large-area functional coating such as automotive or decorative painting of plastic parts, among other topics. In seven concise chapters, the book thoroughly reviews basic thin film technology and deposition processes, sputtering processes, structural control of compound thin films, and microfabrication by sputtering.